'I wish my body looked like theirs!': How positive appearance comments on social media impact adolescents' body dissatisfaction - Kvardova, Nikol; Machackova, Hana; Gulec, Hayriye (Body image, 2023)
Despite robust research evidence for the role of attractive-body portrayals in body image, the effect of positive appearance comments that endorse them on social media remains unclear. Therefore, using a between-subject experimental design and the data from 613 Czech adolescents (52% girls) aged 13-18 (M = 15.5, SD = 1.7), the present study examined exposure to positive appearance comments on body dissatisfaction, and the moderating roles of media-ideal internalization, appearance schematicity, body appreciation, and gender. Our data supported the presumed intensifying effect of the positive appearance comments on post-exposure body dissatisfaction, but only for adolescent girls. The impact of positive comments was not moderated by the media-ideal internalization, appearance schematicity, or body appreciation. However, the exploratory results showed that the displayed bodies' perceived attractiveness intensified the positive comments' effect on body dissatisfaction, which makes it a potentially important factor to target for the prevention of negative social media effects on body image. Furthermore, the individual characteristics that moderated the exposure to attractive images in the prior research may not determine the effects of the positive comments. Future research may need to capture factors that specifically influence the processing of such comments, such as susceptibility to peer feedback on physical appearance.
Keywords: Adolescents; Body Image; mladiství; Social media; fyzický vzhled těla; Body image; mužské pohlaví; Experiment; osobní uspokojení; nespokojenost s tělem; ženské pohlaví; sociální média; Humans; Body Dissatisfaction; Positive appearance comments; Body dissatisfaction; Social Media; Personal Satisfaction; představa o vlastním těle; Female; Physical Appearance, Body; Adolescent; lidé; Male